IBM z/OS V2R2 UNIX system services - Winnard, Keith; Hering, Paul-Robert (IBM redbooks, 2015)
This IBM® Redbooks® publication familiarizes you with the technical changes that were introduced into the UNIX System Services areas with IBM z/OS® V2R2. This book is one of a series of IBM Redbooks publications that take a modular approach to providing information about the updates that are included within z/OS V2R2. This approach has the following goals: - Provide modular content - Group the technical changes into a topic - Provide a more streamlined way of finding relevant information that is based on the topic We hope you find this approach useful. We value your feedback.